G65(P) Unilateral Hypoplastic Kidney – a Novel and Highly Penetrant Feature of Familial Juvenile Hyperuricaemic Nephropathy. (4th June 2013) - Plumb, LA; Marlais, M; Saleem, MA
Abstract : Aim: To highlight an interesting and novel renal phenotype that may provide an insight into the genetics surrounding the development of isolated renal hypoplasia. Methods: A sixteen year old boy was referred to Paediatric Nephrology services following concerns of a strong family history of renal disease. Both his mother and maternal aunt have end stage renal disease. Two of his maternal cousins were found to have chronic kidney disease. All affected members had evidence of hyperuricaemia. The patient's grandparents and maternal uncles were not affected. Renal ultrasounds performed on affected family members revealed unilateral renal hypoplasia in the index case, as well as his mother and aunt. Results: Our case report describes a pedigree with familial juvenile hyperuricaemic nephropathy, a relatively uncommon condition characterised by hypoexcretion of urate leading to hyperuricaemia, gout and progressive renal impairment. This family, however, require our attention for several reasons. Firstly, three affected family members demonstrate unilateral renal hypoplasia inherited in an autosomal dominant manner: to our knowledge this is the first report to describe such a phenotype. Secondly, two affected cousins had normal sized kidneys, suggesting a modifier gene effect, and lastly affected members have tested negative for mutations in two of the major genes implicated in FJHN, which have also been linked to a role in renal morphogenesis: uromodulin ( UMOD ) and hepatocyte nuclear factor 1β ( HNF1b ). Conclusion: Isolated renal hypoplasia is a common congenital anomaly for which a gene association has never been found. The presence of this phenotype in an autosomal dominant manner in this pedigree is therefore of great potential importance, for the ability to identify for the first time a gene responsible for unilateral renal hypoplasia. The association here with renal failure and hyperuricaemia is fascinating, and may provide novel developmental insights linking tubular development, control of lateral renal maturation and renal size. We discuss the known genetics surrounding renal embryogenesis and the implications our pedigree may have for further understanding of this common developmental anomaly.